Decreased Expression of Ileal Thyroid Hormone Transporters in a Hypothyroid Patient: A Case Report - Chung, Chae Won; Mo, Eun Young; Jung, Gyung Seo; Kim, Yoo Hyung; Cho, Sun Wook; Park, Do Joon; Bae, Jeong Mo; Park, Young Joo (Frontiers in Endocrinology, 2021)
Background: Malabsorption of levothyroxine (LT4) is a common problem faced in clinical practice. It is usually solved, if there are no complexities including gastrointestinal absorption disorder, by taking medicines on an empty stomach and avoiding foods interfering with LT4. Herein we present a rare case of a patient exhibiting malabsorption of LT4 with decreased membranous expression of ileal transporters. Case: The 22-Year-old female presented with sustained hypothyroid status despite medication of 7.8 μg/kg LT4. Medical history and LT4 absorption test (the absorption rate 8.4%) excluded pseudomalabsorption. No organic gastrointestinal disorder was found in the patient by blood chemistry, endoscopies and abdominal computed tomography scan. The immunohistochemical analysis showed decreased membranous expression of LAT1 and LAT2 in distal ileum and ascending colon in the patient compared to 20 controls who have no thyroid disease. The expression of MCT8 in colon appeared at both nucleus and brush border in the patient, while it was limited to brush border in controls. The expression of other transporters was similar between the patient and controls. Conclusion: The changes of the expression of LAT1 and LAT2 in this patient showing LT4 malabsorption might help to understand the role of intestinal transporters in the absorption of LT4 in human. The functional relevance of the decrement of LAT1 and LAT2 in this patient remains to be elucidated.